The evolution of diaspora indigenous theoretical approaches from the perspective of the economic development of the Republic of Moldova - FILIP Nelly; CHIRVAS Cristina (EcoSoEn: Ştiinţe Economice, Sociale şi Inginereşti = Economics, Social and Engineering Sciences)
Diaspora permanently contributes to the development of the country from which it comes, considering that it represents a link between societies, which promotes the heritage and values of the country of origin, supports the local community through various decentralized and international cooperation activities, and participates intensively in the development process sustainable with expertise in various fields, economic, human, intellectual capital and vast experience accumulated in the destination country. Unlike the international studies that approach the concept of "diaspora" and that have evolved over time from classic models to its contemporary approaches, in the local specialized literature the studies on the diaspora are quite recent and have mainly taken shape in the last 20-25 years, as a result of the intensification of the migration of citizens of the Republic of Moldova. Thus, the article aims to identify what is the specificity of the theoretical approaches regarding the diaspora in the economic research carried out in the Republic of Moldova, to present an analysis of the most valuable study initiatives on the diaspora-economic development segment and to distinguish the trends by which the academic environment from country tends to strengthen the study process of this field.